Pengujian dan Analisis Unjuk Kerja Runner Tipe Silindris pada Sistem Turbin Air Vortex - Suarda, Made; Sucipta, Made; Srinadi, I Gusti Ayu Made; Liam, Farrell; Pradana, Yossie Rico Rifki (Prosiding Seminar Nasional Sains dan Teknologi (Senastek), 2024)
The vortex turbine system test model has been created in the Machine Performance Laboratory of the Mechanical Engineering Study Program, Faculty of Engineering, Udayana University. As a baseline, a cylindrical turbine runner with curved blades was first tested considering that this runner has a simpler design and is easier to manufacture and has been widely applied. This runner has an outer diameter of 240mm and an inner diameter (shaft bossing) of 42mm and a height of 180mm. The test was carried out with variations in the pump drive water flow rate of around 4 ~ 10 litres/second, and with variations in load or torque. The results show that the greater the load/torque given, the turbine rotation decreases and vice versa. In addition, the greater the flow rate of the turbine drive water produces higher turbine power and torque. However, the highest efficiency is achieved at a water flow rate of around 9 litres/second. The turbine rotation at the highest efficiency is around 120 rpm. So, from the results of the study, this turbine system is recommended to be operated at a flow rate of 8 ~ 9 litres/second.